2017
DOI: 10.1016/j.dib.2016.11.093
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of bovine ovarian follicular and luteal cells

Abstract: Affymetrix Bovine GeneChip® Gene 1.0 ST Array RNA expression analysis was performed on four somatic ovarian cell types: the granulosa cells (GCs) and theca cells (TCs) of the dominant follicle and the large luteal cells (LLCs) and small luteal cells (SLCs) of the corpus luteum. The normalized linear microarray data was deposited to the NCBI GEO repository (GSE83524). Subsequent ANOVA determined genes that were enriched (≥2 fold more) or decreased (≤−2 fold less) in one cell type compared to all three other cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 6 publications
2
34
0
Order By: Relevance
“…Using cell size, the LLC purity was ≥80% (contaminating cells may include clumps of endothelial cells or SLC and similarly sized fibroblasts or immune cells) and the SLC purity was ≥95% (contaminating cells may include clumps of endothelial cells or similarly sized fibroblasts or immune cells. Affymetrix RNA microarray analysis generated the transcriptome data (Romereim et al, 2016) [NCBI GEO GSE83524]. An overall low standard deviation profile indicated quality amplification, with slightly higher standard deviations for lower-intensity RNAs suggesting more variability for low copy-number targets [see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using cell size, the LLC purity was ≥80% (contaminating cells may include clumps of endothelial cells or SLC and similarly sized fibroblasts or immune cells) and the SLC purity was ≥95% (contaminating cells may include clumps of endothelial cells or similarly sized fibroblasts or immune cells. Affymetrix RNA microarray analysis generated the transcriptome data (Romereim et al, 2016) [NCBI GEO GSE83524]. An overall low standard deviation profile indicated quality amplification, with slightly higher standard deviations for lower-intensity RNAs suggesting more variability for low copy-number targets [see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that CYP19A1 and PTGFR could be considered as cellular markers of GCs and luteal cells, respectively. [ 29 ] During the luteal steroidogenesis, StAR delivers cholesterol to the mitochondrial intima, and then P450scc catalyzes pregnenolone synthesis and HSD3B catalyzes progesterone synthesis. Androstenedione was the substrate of estrogen, and CYP19A1 catalyzes estrogen synthesis in the mural and cumulus GCs.…”
Section: Discussionmentioning
confidence: 99%
“…The components of hippo signaling in granulosa cells have been reported in both the mouse [18], hen [27], and human [28]. Moreover, microarray studies of bovine granulosa cells have revealed the transcripts for hippo signaling [29, 30]. Here, we examined YAP and TAZ protein expression in bovine ovaries.…”
Section: Discussionmentioning
confidence: 99%